FAKTOR-FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN DAN IMPLIKASINYA TERHADAP ASIMETRI INFORMASI PADA PERUSAHAAN PUBLIK DI INDONESIA - Wany, Eva (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2015)
This study aimed to examine the effect of the characteristics of the company include: the size of the company, the level of leverage of the company, the share of public ownership, the company's liquidity, profitability of the company and the size of the office of public accountant (auditor) to the broad disclosure of the annual report. In addition, this research also examine the effect of disclosure to the asymmetry of information. The sampling technique used purposive sampling with criteria the company has published its annual report continuously since 2011 until 2013 on the official website of the the Indonesia Stock Exchange (BEI), the Company did not obtain adverse opinion or disclaimer of opinion, the Company has never experienced delisting from the Indonesia Stock Exchange and the Company has a daily transaction data companies such as the ask price and the bid price is available on the Indonesia Stock Exchange. Techniques analysis to test hypothesis using multiple linear regression. The results showed that the characteristics of the company in the form of company size and the size of the KAP positive effect on disclosure, while the level of leverage, the share of public ownership, liquidity and profitability does not affect the broad disclosure. The results also show the effect of the broad disclosure on information asymmetry.